Preparation method of electron transport layer applied to trans-perovskite solar cell, electron transport layer and perovskite solar cell

By using the modified SnO2 electron transport layer in trans perovskite solar cells, polyelectrolyte materials are used to improve the energy level matching and hydrophobic properties with the perovskite film, the problems of low efficiency and poor stability of the SnO2 electron transport layer are solved, and the photoelectric conversion efficiency is improved and the preparation cost is reduced.

CN119677369APending Publication Date: 2025-03-21BEIJING BOYA JIE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411920958.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, the SnO2 electron transport layer in trans perovskite solar cells has low efficiency and poor stability, resulting in a photoelectric conversion efficiency of less than 20%, and at the same time, the preparation process is complex and the cost is high.

Method used

Using a modified SnO2 electron transport layer, polyelectrolyte materials such as poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-(9,9-din-octylfluorenyl2,7-diyl)]dibromide (PFN-Br) or polyethylene glycol methylene acrylate copolymer (PEIE) are added to the SnO2 nanoparticle solution to improve the energy level matching and hydrophobic properties with the perovskite film.

Benefits of technology

Through the modified SnO2 electron transport layer, the photoelectric conversion efficiency of trans-structured perovskite solar cells is increased to 24.70%, while improving humidity stability and reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677369A_ABST
    Figure CN119677369A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, in particular to a preparation method of an electron transport layer applied to a trans-perovskite solar cell, the electron transport layer and the perovskite solar cell. Drying in a forced air drying oven, and treating with ultraviolet ozone to obtain a transparent conductive oxide substrate; placing the transparent conductive oxide substrate in a glove box in a nitrogen atmosphere to prepare a hole transport layer; spin-coating the hole transport layer with a perovskite precursor solution, and after spin-coating, placing the obtained perovskite light absorption film layer on a heating stage for annealing; the PFN-Br or PEIE polyelectrolyte material is added into the SnO2 nanoparticle solution to obtain the modified SnO2 electron transport layer, and the modified SnO2 electron transport layer has better hydrophobic property, so that the humidity stability of the perovskite solar cell is improved, and the photoelectric conversion efficiency of the trans-structure perovskite cell is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a method for preparing an electron transport layer applied to an inverted perovskite solar cell, an electron transport layer and a perovskite solar cell. Background Art

[0002] In recent years, solar cells based on organic-inorganic hybrid perovskite materials have developed rapidly. Currently, the highest photoelectric conversion efficiency of a single-cell perovskite solar cell is 26.7%, which is very close to the best performance level of silicon-based solar cells.

[0003] The structures of perovskite solar cells include trans structure and formal structure. Compared with formal structure perovskite solar cells, trans structure perovskite solar cells have the advantages of simple preparation process, small hysteresis, low annealing temperature, compatibility with flexible substrates and the ability to build high-efficiency stacked cells. In this type of cell, p-interface materials often use nickel oxide, self-assembled monolayers and other materials, and n-interface materials are mostly fullerenes and their derivatives (such as C60, PCBM). Among these interface materials, the preparation process of fullerenes and their derivatives is the most complicated. The preparation methods of fullerenes include arc method, combustion method, laser evaporation method, etc., which have high technical requirements, complex operation, and strict requirements on equipment and environment, which makes mass production difficult and thus very expensive.

[0004] Secondly, the researchers also found that the oxygen adsorbed in fullerenes can cause deep energy level defects in perovskite solar cells, reducing battery performance and performance repeatability. Therefore, further sublimation operations are required on C60 to reduce its adsorbed oxygen content, which will further increase the complexity of the preparation of such electron transport layers and increase the cost of battery preparation.

[0005] In order to solve the above problems, the use of non-fullerene electron transport layer is a good solution. Among them, the tin oxide (SnO2) electron transport layer has unique advantages such as deep conduction band bottom, high chemical stability, wide bandgap, high light transmittance in the visible light region, UV resistance, and low photochemical activity. The methods for preparing the SnO2 electron transport layer mainly include atomic layer deposition, chemical bath deposition, and coating SnO2 nanoparticle solution. However, in the inverse structure perovskite solar cell, the electron transport layer is prepared on the perovskite film. In the process of preparing the SnO2 electron transport layer by atomic layer deposition or chemical bath deposition, the perovskite film may be damaged to a certain extent. Therefore, the solution method for preparing the SnO2 electron transport layer may be a more ideal choice. However, due to the spontaneous agglomeration of SnO2 nanoparticles, the band mismatch with perovskite films, the hydrophilicity of SnO2, the interface energy level mismatch between SnO2 and perovskite films, the non-radiative recombination induced by SnO2's own defects (such as O vacancies and surface hydroxyl groups), and the side reaction with perovskite, the efficiency of the SnO2 electron transport layer prepared by the solution method is less than 20%, and its stability is also not ideal. Summary of the invention

[0006] In order to solve the problems of low efficiency and poor stability of the SnO2 electron transport layer prepared by the above-mentioned prior art, the present invention provides a method for preparing an electron transport layer applied to an inverted perovskite solar cell, an electron transport layer and a perovskite solar cell.

[0007] The present invention adopts the following technical solutions: A method for preparing an electron transport layer for an inverse perovskite solar cell comprises the following steps: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropyl alcohol ultrasonically in sequence; dried in a blast drying oven; the dried transparent conductive glass is treated with ultraviolet ozone to obtain a transparent conductive oxide substrate; S2: Preparation of hole transport layer: placing the transparent conductive oxide substrate in a glove box with a nitrogen atmosphere, wherein the water and oxygen content in the glove box is less than 0.01 ppm, and preparing a hole transport layer on the transparent conductive oxide substrate, wherein the material of the hole transport layer is selected from one of polythiophene acetic acid, nickel oxide, polytriphenylamine, and self-assembled monolayer, and the material is prepared by a solution method; S3: Preparation of a perovskite light absorbing thin film layer: adding a perovskite precursor material to a corresponding solvent in a preset proportion, stirring and oscillating, to obtain a perovskite precursor solution; Spin coating the perovskite precursor solution onto the hole transport layer using a coating machine, adding an anti-solvent dropwise during the spin coating, and placing the obtained perovskite light absorption film layer on a hot stage for annealing after the spin coating, with the annealing temperature being 100° C. to 300° C.; S4: Preparation of modified SnO2 electron transport layer: SnO2 nanoparticles are placed in a dispersion, wherein the dispersion includes one of butanol, ethanol, isopropanol, and DMF, with a mass fraction of 2.5 wt%-10 wt%. A polyelectrolyte material is added to the SnO2 nanoparticle solution, wherein the polyelectrolyte material is selected from one of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-(9,9-di-n-octylfluorenyl-2,7-diyl)] dibromide) and polyethylene glycol methylene acrylate copolymers, with a concentration of 0.1 to 5 mg mL -1 .

[0008] In some embodiments, in S1, the time intervals for ultrasonic cleaning with deionized water, acetone, glass cleaner, deionized water, and isopropyl alcohol are set to 10-30 min, and the time is the same. The glass is placed in a 60°C forced air drying oven for drying, and the dried transparent conductive glass is treated with ultraviolet ozone for 15 min.

[0009] In some embodiments, in S1, the transparent conductive glass is selected from FTO or ITO conductive glass.

[0010] In some embodiments, in S2, a hole transport layer is prepared using a spin coater, and a spin coating material solution of a preset concentration is spin coated at a spin coating speed of 1000-8000 rpm for 30-90 s. After the spin coating is completed, the solution is transferred to a hot plate at 80-150° C. and heated for 5-30 min.

[0011] In some embodiments, in S2, the spin coating speed of the spin coater is 3000 rpm, the spin coating time is 30 s, and after the spin coating is completed, the substrate is transferred to a 100° C. hot plate and heated for 10 min.

[0012] In some embodiments, in S3, the perovskite precursor material is selected from at least two of lead iodide, lead chloride, lead bromide, iodoformamidine, formamidine chloride, formamidine bromide, methylamine iodine, methylamine chloride, methylamine bromide, cesium iodide, cesium chloride, cesium bromide, rubidium iodide, rubidium chloride, and rubidium bromide and mixed in a preset ratio; the solvent is selected from at least two of dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone and mixed in a preset ratio.

[0013] The perovskite precursor solution is spin-coated onto the hole transport layer using a spin coater, and the process of adding an anti-solvent during the spin coating includes: First, add an appropriate amount of perovskite precursor solution to the hole transport layer, and then turn on the spin coater for spin coating. The first step: the speed range is 300-1000 rpm, and the speed increase rate is 200 rpm s -1 , rotate for 10 s; Step 2: Select the speed range of 2000-8000 rpm, and the speed increase rate is 1000 rpm s -1 The total spin coating time range of the first step and the second step is set to 30-90s, and 150 μL of anti-solvent is added 10 s before the end of spin coating. The amount of anti-solvent is 100 microliters to 5 milliliters.

[0014] In some embodiments, in S3, the coating process of the coating machine is as follows: the rotation speed range is 1000 rpm, and the speed increase rate is 200 rpm s -1 , rotate for 10 s; Step 2: Select the speed range as 5000 rpm, and the speed increase rate is 1000 rpm s -1 The total spin coating time range of the first step and the second step was set to 35 s, and 150 μL of anti-solvent was added 10 s before the end of the spin coating.

[0015] In some embodiments, in S4, poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-(9,9-di-n-octylfluorenyl-2,7-diyl)] dibromide) (PFN-Br), polyethylene glycol methylene acrylate copolymer (PEIE), the molecular formulas of PEIE and PFN-Br are as follows: .

[0016] The present invention also includes an electron transport layer, which is prepared using the above-mentioned preparation method for the electron transport layer of an inverse perovskite solar cell.

[0017] The present invention also includes a perovskite solar cell, which comprises the above-mentioned electron transport layer. Beneficial Effects

[0018] The present invention discloses a preparation method of an electron transport layer applied to an inverted perovskite solar cell, an electron transport layer and a perovskite solar cell. Compared with the prior art, the present invention has the following advantages: In the preparation process of the electron transport layer applied to the inverse perovskite solar cell of the present invention, the SnO2 electron transport layer modified by PEIE or PFN-Br has better energy level matching with the perovskite film, and the spontaneous agglomeration problem of SnO2 nanoparticles is greatly alleviated. Due to the hydrophobic alkyl chain of the PEIE or PFN-Br polymer, the modified SnO2 electron transport layer has better hydrophobic properties, thereby improving the humidity stability of the perovskite solar cell. The non-fullerene electron transport layer inverse structure perovskite cell prepared based on this process has a maximum photoelectric conversion efficiency of 24.70%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments, which constitute a part of the present invention. The schematic embodiments of the present invention and their descriptions explain the present invention and do not constitute improper limitations on the present invention. In the drawings: Figure 1 A flow chart of a method for preparing an electron transport layer provided in an embodiment of the present invention; Figure 2 A schematic diagram of a structure formed during the preparation process of an electron transport layer provided in an embodiment of the present invention; Figure 3 A JV curve diagram of the perovskite battery provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0020] The following is a description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, including various details of the embodiments of the present invention to facilitate understanding, which should be considered as merely exemplary. Therefore, it should be recognized by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present invention. Similarly, for clarity and conciseness, the description of well-known functions and structures is omitted in the following description.

[0021] In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they cannot be understood as limitations on the present invention.

[0022] like Figure 1 - Figure 3 As shown, the technical solution of the present invention: A method for preparing an electron transport layer for an inverse perovskite solar cell comprises the following steps: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropyl alcohol ultrasonically in sequence; dried in a blast drying oven; the dried transparent conductive glass is treated with ultraviolet ozone to obtain a transparent conductive oxide substrate; S2: Preparation of hole transport layer: placing the transparent conductive oxide substrate in a glove box with a nitrogen atmosphere, wherein the water and oxygen content in the glove box is less than 0.01 ppm, and preparing a hole transport layer on the transparent conductive oxide substrate, wherein the material of the hole transport layer is selected from one of polythiophene acetic acid, nickel oxide, polytriphenylamine, and self-assembled monolayer, and the material is prepared by a solution method; S3: Preparation of a perovskite light absorbing thin film layer: adding a perovskite precursor material to a corresponding solvent in a preset proportion, stirring and oscillating, to obtain a perovskite precursor solution; Spin coating the perovskite precursor solution onto the hole transport layer using a coating machine, adding an anti-solvent dropwise during the spin coating, and placing the obtained perovskite light absorption film layer on a hot stage for annealing after the spin coating, with the annealing temperature being 100° C. to 300° C.; S4: Preparation of modified SnO2 electron transport layer: SnO2 nanoparticles are placed in a dispersion, wherein the dispersion includes one of butanol, ethanol, isopropanol, and DMF, with a mass fraction of 2.5 wt%-10 wt%. A polyelectrolyte material is added to the SnO2 nanoparticle solution, wherein the polyelectrolyte material is selected from one of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-(9,9-di-n-octylfluorenyl-2,7-diyl)] dibromide) and polyethylene glycol methylene acrylate copolymers, with a concentration of 0.1 to 5 mg mL -1 .

[0023] The preferred embodiments disclosed in the present invention are as follows: Figure 1-Figure 3 As shown: The present invention discloses a method for preparing an electron transport layer for an inverse perovskite solar cell, comprising the following steps: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is ultrasonically cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropanol in sequence. FTO or ITO conductive glass is usually selected. In this embodiment, FTO transparent conductive glass is selected. The ultrasonic cleaning time is set to 10-30 min. In this embodiment, the ultrasonic cleaning time is set to 10 min. After the ultrasonic cleaning is completed, it is placed in a 60°C blast drying oven for drying. The dried FTO transparent conductive glass is treated with ultraviolet ozone for 15 min to obtain a transparent conductive oxide substrate; S2: Preparation of hole transport layer: The transparent conductive oxide substrate is placed in a glove box with a nitrogen atmosphere, wherein the water and oxygen content in the glove box is less than 0.01 ppm, and a hole transport layer is prepared on the transparent conductive oxide substrate. The material of the hole transport layer is selected from one of polythiophene acetic acid (PTAA), nickel oxide (NiOx), polytriphenylamine (Poly-TPD), and self-assembled monolayer. The material preparation method includes solution method, sol-gel method, magnetron sputtering method, atomic layer deposition method, and combustion method. The solution method is preferred. In this embodiment, the self-assembled monolayer material selected is MeO-2PACz, and the concentration range is 0.3 mg mL -1 ~5 mg mL -1 , the solvent is ethanol; a spin coater, a slit coater, a doctor blade coater, and an inkjet printer can be used.

[0024] The hole transport layer was prepared using a LEBO spin coater and the concentration range was 0.3 mg mL -1 ~5 mg mL -1 The spin coating material solution is spin coated at a spin coating speed range of 1000-8000rpm and a spin coating time of 30-90s. After the spin coating is completed, the solution is transferred to a hot plate at 80-150°C and heated for 5-30 min. In this embodiment, the spin coating apparatus is used to coat the solution with a concentration of 0.3 mg mL -1 The solution was spin coated at a speed of 3000 rpm for 30 s. After the spin coating, it was transferred to a hot stage at 100°C and heated for 10 min.

[0025] S3: Preparation of perovskite light absorbing thin film layer: First, the perovskite precursor materials including lead iodide (PbI2), lead chloride (PbCl2), lead bromide (PbBr2), iodomethane (FAI), methylammonium chloride (FACl), methylammonium bromide (FABr), methylamine iodide (MAI), methylamine chloride (MACl), methylamine bromide (MABr), cesium iodide (CsI), cesium chloride (CsCl), cesium bromide (CsBr), rubidium iodide (RbI), rubidium chloride (RbCl), and rubidium bromide (RbBr) are mixed in a preset ratio; a corresponding solvent is added, and the solvent is selected from at least two of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N-methylpyrrolidone (NMP), and mixed in a preset ratio; the two mixed solutions are mixed in a preset ratio, and stirred and shaken to obtain a perovskite precursor solution.

[0026] The perovskite precursor materials selected in this embodiment are cesium iodide (CsI), iodoformamidine (FAI), lead iodide (PbI2), and lead bromide (PbBr2). The solution concentration is 1.5 M. 0.075 mmol cesium iodide, 1.425 mmol iodoformamidine, 1.425 mmol lead iodide, and 0.075 mmol lead bromide are mixed together; the added solvent is DMF:DMSO, and the ratio is 4:1; after stirring and shaking, a perovskite precursor solution (CsI) is obtained. 0.05 FA 0.95 Pb(Br 0.05 I 0.95 )3).

[0027] The perovskite precursor solution is spin-coated onto the hole transport layer using a spin coating machine, using a multi-step spin coating process, and an anti-solvent is added dropwise during the spin coating process, the process comprising: Step 1: First, add an appropriate amount of perovskite precursor solution to the hole transport layer, and then turn on the spin coater for spin coating. The spin coating speed range is 300-1000 rpm, and the speed increase rate is 200 rpm s -1 In this embodiment, the speed is 1000 rpm and the rotation is 10 seconds.

[0028] Step 2: Spin coating speed range is 2000-8000 rpm, and the speed increase rate is 1000 rpm s -1 , in this embodiment, the spin speed is 5000 rpm, the total spin coating time range of the first step and the second step is set to 30-90s, and the total spin coating time in this embodiment is 35s; 10 s before the end of spin coating, the anti-solvent is added dropwise, the amount of the anti-solvent is 100 microliters to 5 milliliters, the anti-solvent is selected as chlorobenzene in this embodiment, and the amount of anti-solvent chlorobenzene added is 150 μL, after the spin coating is completed, the obtained perovskite light absorption film layer is placed on a hot stage for annealing, and the annealing temperature is 100°C to 300°C. In this embodiment, heating on a hot stage at 120°C for 10 minutes is selected.

[0029] S4: Preparation of modified SnO2 electron transport layer: SnO2 nanoparticles are placed in a dispersion, wherein the dispersion includes one of butanol, ethanol, isopropanol, and DMF. In this embodiment, butanol is selected, and the mass fraction is 2.5 wt%-10 wt%. In this embodiment, 2.5 wt% is selected. A polyelectrolyte material is added to the SnO2 nanoparticle solution. The polyelectrolyte material is selected from one of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-(9,9-di-n-octylfluorenyl-2,7-diyl)] dibromide) (PFN-Br) and polyethylene glycol methylene acrylate copolymer (PEIE), and the molecular formula is as follows:

[0030] Concentrations range from 0.1 to 5 mg mL -1 PFN-Br was selected in this example at a concentration of 0.5 mg mL -1 .

[0031] Perovskite solar cells are made using conventional methods using perovskite films, such as Figure 1 , Figure 2 shown.

[0032] Perovskite solar cells were fabricated using a modified SnO2 electron transport layer according to conventional methods.

[0033] Experiments have found that the highest photoelectric conversion efficiency of the inverse-structured perovskite solar cell prepared with a non-modified SnO2 electron transport layer is 21%, while the inverse-structured perovskite cell with a modified SnO2 electron transport layer can achieve a photoelectric conversion efficiency of 24.70%. Figure 3 As shown, Figure 3 The photoelectric conversion efficiency jv curve of the modified SnO2 electron transport layer inverse structure perovskite cell provided in an embodiment of the present invention.

[0034] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing an electron transport layer for an inverse perovskite solar cell, characterized in that: The steps include: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropyl alcohol ultrasonically in sequence; dried in a blast drying oven; the dried transparent conductive glass is treated with ultraviolet ozone to obtain a transparent conductive oxide substrate; S2: Preparation of hole transport layer: placing the transparent conductive oxide substrate in a glove box with a nitrogen atmosphere, wherein the water and oxygen content in the glove box is less than 0.01 ppm, and preparing a hole transport layer on the transparent conductive oxide substrate, wherein the material of the hole transport layer is selected from one of polythiophene acetic acid, nickel oxide, polytriphenylamine, and self-assembled monolayer, and the material is prepared by a solution method; S3: Preparation of a perovskite light absorbing thin film layer: adding a perovskite precursor material to a corresponding solvent in a preset proportion, stirring and oscillating, to obtain a perovskite precursor solution; Spin coating the perovskite precursor solution onto the hole transport layer using a coating machine, adding an anti-solvent dropwise during the spin coating, and placing the obtained perovskite light absorption film layer on a hot stage for annealing after the spin coating, with the annealing temperature being 100° C. to 300° C.; S4: Preparation of modified SnO2 electron transport layer: SnO2 nanoparticles are placed in a dispersion, wherein the dispersion includes one of butanol, ethanol, isopropanol, and DMF, with a mass fraction of 2.5 wt%-10 wt%. A polyelectrolyte material is added to the SnO2 nanoparticle solution, wherein the polyelectrolyte material is selected from one of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-(9,9-di-n-octylfluorenyl-2,7-diyl)] dibromide) and polyethylene glycol methylene acrylate copolymers, with a concentration of 0.1 to 5 mg mL -1 .

2. The preparation method according to claim 1, characterized in that: In S1, the time intervals for ultrasonic cleaning with deionized water, acetone, glass cleaning agent, deionized water, and isopropanol are set to 10-30 min respectively, and the time is the same. The glass is placed in a 60°C forced air drying oven for drying, and the dried transparent conductive glass is treated with ultraviolet ozone for 15 min.

3. The preparation method according to claim 1, characterized in that: In S1, the transparent conductive glass is selected from FTO or ITO conductive glass.

4. The preparation method according to claim 1, characterized in that: In S2, a hole transport layer is prepared using a spin coater, and a spin coating material solution of a preset concentration is spin coated at a spin coating speed of 1000-8000 rpm for 30-90 s. After the spin coating is completed, the solution is transferred to a hot plate at 80-150° C. and heated for 5-30 min.

5. The preparation method according to claim 4, characterized in that: In S2, the spin coating speed of the spin coater is 3000 rpm, the spin coating time is 30 s, and after the spin coating is completed, it is transferred to a 100° C. hot stage and heated for 10 min.

6. The preparation method according to claim 1, characterized in that: In S3, the perovskite precursor material is selected from at least two of lead iodide, lead chloride, lead bromide, iodoformamidine, formamidine chloride, formamidine bromide, methylamine iodine, methylamine chloride, methylamine bromide, cesium iodide, cesium chloride, cesium bromide, rubidium iodide, rubidium chloride, and rubidium bromide, and mixed in a preset ratio; the solvent is selected from at least two of dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone, and mixed in a preset ratio; The perovskite precursor solution is spin-coated onto the hole transport layer using a spin coater, and the process of adding an anti-solvent during the spin coating includes: First, add an appropriate amount of perovskite precursor solution to the hole transport layer, and then turn on the spin coater for spin coating. The first step: the speed range is 300-1000 rpm, and the speed increase rate is 200 rpm s -1 , rotate for 10 s; Step 2: Select the speed range of 2000-8000 rpm, and the speed increase rate is 1000 rpm s -1 The total spin coating time range of the first step and the second step is set to 30-90s, and 150 μL of anti-solvent is added 10 s before the end of spin coating. The amount of anti-solvent is 100 microliters to 5 milliliters.

7. The preparation method according to claim 6, characterized in that: In S3, the process of spin coating by the glue machine, the first step: the speed range is selected as 1000 rpm, and the speed increase rate is 200 rpm s -1 , rotate for 10 s; Step 2: The speed range is selected to be 5000 rpm, and the speed increase rate is 1000 rpm s -1 The total spin coating time range of the first step and the second step was set to 35 s, and 150 μL of anti-solvent was added 10 s before the end of the spin coating.

8. The preparation method according to claim 1, characterized in that: In S4, the molecular formulas of poly[(9,9-bis(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-alt-(9,9-di-n-octylfluorenyl-2,7-diyl)] dibromide) (PFN-Br) and polyethylene glycol methylene acrylate copolymer (PEIE) are as follows: 。 9. An electron transport layer, characterized in that: It is prepared using the preparation method for an electron transport layer for an inverse perovskite solar cell according to any one of claims 1 to 6.

10. A perovskite solar cell, characterized in that: The electron transport layer according to claim 7 is included.